“Nono, vem aqui que tem gente”: cultura e identidade na comunidade São Pio X – km 20, Francisco Beltrão, Paraná - Oliveira, Aline Tortora de (2018)
This dissertation analyzes the cultural identity of São Pio X – Km 20 community, from Francisco Beltrão, Paraná. In the investigation, we established as a research problem the question: How do community dwellers build cultural identity? We have as a general objective to record the history of São Pio X community, including the process of identity and cultural identification. The specific objectives stated were: a) to identify the cultural markers selected by residents of São Pio X community as elements of identity; b) to point out the correlations between the cultural heritage of the Italian descendants and the process of community identification; c) to establish the meanings of the school and the church to the cultural identity assumed by the residents of São Pio X community; d) to analyze the significance of the parties to the construction of the process of identity and identification. It is a qualitative research of ethnographic type, in which we use the following instruments for data collection: a) observation and description; b) photographic record (registered by the researcher and kept in the personal collection of the community residents; c) documentary analysis (Atas Books, Beltrão Journal and official documents); d) Field Diary; e) narrative interviews. We selected the church, the school and the feast of the Italian Culture – Fest Vin, as the main sociality spaces, in which the inhabitants participate and shape their identities. Food, religious beliefs and festivities make up the daily customs of the residents. The main intention of the research is to understand how the inhabitants construct the cultural identity in these spaces and places and the relations with the identities that these subjects assume. In order to give theoretical and methodological support to the actions we use the contributions of Bauman (2005), Costa (1985), Geertz (1981), Hall (2015), Iotti (2001, 2010), Kossoy 1986), Marques (2008), Martins (1986), Scheneider (2012), Vannini (2003), Wenczenovicz (2014), among others. In the years 2016 and 2017, we sought the information that compose the dissertation. The totality of the collected and analyzed material indicates that the locus of the research uses cultural markers to frame the processes of identity and identification. These include: the production and usufruct of food, the usage of Italian language expressions to demarcate a connection with the past and its ancestors that came from Italy; The religiosity as an aggregating element and producer of the social bond and the experience of the party. It is necessary to emphasize the place occupied by the school: production and dissemination of a representation of the Italian ethnicity. Such markers have been identified as determinants of how subjects see and perceive themselves.